Optimal Load Dispatch for Hydro Power Plants. - Nkwasibwe Wilber (Kabale University, 2023)
This report is about an optimization of hydro power generation by using least possible amount of water to generate the demand power. The case study of the project has two generating units and total generation capacity of 6.5 MW, Unit 1 generates 2.5 MW and Unit 2 generates 4.0 MW. The turbines and generators of the generating units have different efficiencies which contribute to different rates at which water is discharged by generator turbines. The solution is obtained by comparing the amount of water discharged by each generating unit for the old approach currently being used by power plant operators and after comparing, a new approach is suggested in this report for optimization. The optimization method used is the lambda method and the software used is Matlab which gives the values of load power to be generated by each generating unit.